Praziquantel Targets M1 Macrophages and Ameliorates Splenomegaly in Chronic Schistosomiasis - Kong, Delong (Antimicrob Agents Chemother, 2017)
Splenomegaly is a common feature of many infectious diseases, including schistosomiasis japonica. However, the immunopathogenesis and the treatment of splenomegaly due to schistosomiasis have been largely neglected. Praziquantel (PZQ), a classical schistosomicide, has been demonstrated by us and others to have antifibrotic and anti-inflammatory activities against schistosomiasis. In this study, we investigated the effect of PZQ on alleviating the splenomegaly caused by Schistosoma japonicum infection in mice. The results showed that the number of macrophages, especially the number of M1 macrophages, was significantly increased in the enlarged spleens of infected mice (P < 0.001). After PZQ treatment for 4 weeks, the number of splenic macrophages, especially the number of M1 macrophages, was significantly reduced (P < 0.001) by the way of apoptosis, and another schistosomicide, mefloquine, had no effect either on the splenomegaly or on reducing the number of macrophages. Furthermore, by using the murine macrophage line RAW 264.7, we found that PZQ could inhibit the formation of the NLRP3 inflammasome and attenuate phagocytic activity in M1 macrophages. Thus, our studies suggest that PZQ plays a powerful role in ameliorating the splenomegaly caused by S. japonicum infection, which presents a new strategy for the therapy of splenomegaly resulting from other pathological conditions.